Enabling EMT: N-BLR promotes metastasis in colorectal cancer via regulation of epithelial-to-mesenchymal transition - Haswell, Jeffrey R.; Slack, Frank J. (Non-coding RNA Investigation, 2017)
Over the past twenty years, the advent of deep sequencing technology has revealed the pervasive and widespread nature of transcription across the human genome, with ~80% being transcribed at some point during development (1). Given that 200 nt) ncRNAs have emerged as major regulators of several key biological processes, including differentiation and oncogenesis (2,3).